Tumor microenvironment metabolites directing T cell differentiation and function. Issue 2 (February 2022) - Liu, Xia; Hoft, Daniel F.; Peng, Guangyong
Abstract : Metabolic reprogramming of cancer cells creates a unique tumor microenvironment (TME) characterized by the limited availability of nutrients, which subsequently affects the metabolism, differentiation, and function of tumor-infiltrating T lymphocytes (TILs). TILs can also be inhibited by tumor-derived metabolic waste products and low oxygen. Therefore, a thorough understanding of how such unique metabolites influence mammalian T cell differentiation and function can inform novel anticancer therapeutic approaches. Here, we highlight the importance of these metabolites in modulating various T cell subsets within the TME, dissecting how these changes might alter clinical outcomes. We explore potential TME metabolic determinants that might constitute candidate targets for cancer immunotherapies, ideally leading to future strategies for reprogramming tumor metabolism to potentiate anticancer T cell functions. Highlights: Metabolic dysfunction is a key hallmark of cancer, resulting in the accumulation of metabolites in the tumor microenvironment (TME), affecting both cancer cells and immune components. Abnormal production of metabolites in the TME is associated with negative clinical outcomes and disease progression of cancer patients. TME metabolites derived from glucose and lipid metabolism can direct the differentiation, function, and fate of tumor-infiltrating T cells, thereby affecting antitumor immunity and immunotherapy. Reprogramming of tumor metabolism in the TME, especially targeting key metabolites, has emerged as a novel and promising strategy for the treatment of certain tumors.